Analisis Efisiensi Sistem Informasi Manajemen Nikah (Simkah) Pada Kantor Urusan Agama Kecamatan Sidoarjo - Lolyta, Indri Cahya; Prabowo, Prayudi Setiawan (Universitas Negeri Surabaya, 2019)
This quantitative research aims to analyze how efficient public services at Office of Religious Affair in Sidoarjo sub-district using SIMKAH. Data analysis technique using data envelopment analysis (DEA) with input variables: cost, service time, number of employees while output variable: number of marriage books in 2018. The sampling teknik used is purposive sampling through interview data collection techniques and documentation. The results of optained, office of religious affair Sidoarjo sub-district can as a reference for other office of religious affair